Train-track interactions over vulnerable railway turnout systems exposed to flooding conditions. (September 2021) - Hamarat, Mehmet; Papaelias, Mayorkinos; Kaewunruen, Sakdirat
Highlights: 3D FE model coupled with multi-body simulation has been developed. Vulnerability of railway turnout systems has been assessed. This study is the first to assess train-turnout interactions exposed to flood damage conditions. The new insights will help track engineers to define operational restrictions building resilience capability. Abstract: Track twists used in modern railways indicate the warpage of a particular track plane to identify track quality. In some cases, a twist is intentionally introduced on tracks to facilitate motions in curves. Nevertheless, twists can exceed above certain thresholds resulting in twist faults, which impose direct risk to safety and a potential cause for derailments. Twist faults are commonly observed in ballasted tracks, which consists of crushed rock particles and have low endurance to resist against dynamic track forces. In general, the deterioration in ballast structure progresses slowly. However, in reality, there are some catalysts such as extreme events that can speed up the deterioration of the ballast bed. Extreme events have rare occurrences but a high potential to damage structures and environment in a short duration. Even though the term 'rare' is still used to define extreme events, a consensus among the environmental scientists on the increased frequency of extreme events could be found in open literatures. In this study, the impacts of flooding, one of the most common extreme events, on the dynamic phenomena of a turnout structure is investigated in terms of dynamic twists. The emphasis is placed on railway turnouts of which the asymmetrical structure is expected to amplify twist responses. A 3-dimensional finite element method (FEM) model has been developed and many hypothetical scenarios ranging from various materials to vehicle speeds have been tested in virtual environments. It should be noted that the developed model is the modified version of a previously validated model and therefore, validation of the model is done by a comparison with the parent model. This study is the world's first to demonstrate that the dynamic performance of composite and plastic bearers is relatively poor in comparison to concrete bearers when considering dynamic twist phenomena. Our new results also exhibit that partially damaged turnout structures in the case of flooding is the most critical and vulnerable situation, which could result in detrimental train derailments. This vulnerability cannot practically be inspected by naked and untrained eyes. On this ground, when exposed to flooding conditions, it is recommended to halt any railway operations over vulnerable switches and crossings, and to avoid the approach of 'reach the station first' in emergency cases.